A note on the first record of the dwarf minke whale (Balaenoptera acutorostrata) in Chilean waters - Pastene , Luis A.; Acevedo , Jorge; Aguayo-Lobo , Anelio; Acuna , Paolo (J. Cetacean Res. Manage., 2023)
Two species of minke whale have been recognised, the larger Antarctic minke whale (Balaenoptera bonaerensis) restricted to the Southern Hemisphere, and the common minke whale (B. acutorostrata), which is distributed globally. The common minke whale of the Southern Hemisphere is referred to as the dwarf minke whale. The occurrence and identity of minke whales in the coastal waters of Chile are examined based on animals stranded and sighted in the Patagonia Channels. A total of three strandings and five sightings of the minke whale were examined in this study. Comparative analysis of external characteristics between the stranded animals and the two recognised species of minke whale identified these animals as dwarf minke whales. Of the five sightings, two were identified as Antarctic and two as dwarf minke whales based on observation of the presence/absence of the white patch on the flippers. This is the first record of the dwarf minke whale in the coastal waters of Chile. Based on available information on temporal distribution of sightings in the western south Atlantic, it is suggested that the population of dwarf minke whales wintering off Brazil may move to the south in summer, some moving into the Patagonia Channels.